Distribution Scheme And Achieve Balance Of Financial Income From A Sharia Perspective - Septiana, Eka Salsa Putri; A'la, Hadika A'zul; Rohmah, Siti (Universitas Gorontalo, 2024)
This research identifies distribution schemes and achieving balance in financial income from a sharia perspective. This research uses descriptive qualitative methods with literature study as the main tool in data collection. The data sources used come from books, journals, notes and summaries of previous study findings. The results show that Islam regulates the distribution of assets, social security, and wealth to achieve justice, equality, and social welfare. Sharia principles include justice, equality, and prosperity. The main instruments include zakat, the prohibition of usury, and inheritance rules. The distribution scheme in sharia economics emphasizes justice, blessing and sustainability. Through zakat, infaq, profit-sharing and mudharabah mechanisms, income is redistributed fairly. Achieving balanced financial returns requires cross-sector engagement and a holistic approach. However, challenges such as social inequality, economic uncertainty and infrastructure limitations must be overcome.